2013
DOI: 10.3402/tellusb.v65i0.20792
|View full text |Cite
|
Sign up to set email alerts
|

Sustained large stimulation of soil heterotrophic respiration rate and its temperature sensitivity by soil warming in a cool-temperate forested peatland

Abstract: A B S T R A C T We conducted a soil warming experiment in a cool-temperate forested peatland in northern Japan during the snow-free seasons of 2007Á2011, to determine whether the soil warming would change the heterotrophic respiration rate and its temperature sensitivity. We elevated the soil temperature by 38C at 5-cm depth by using overhead infrared heaters and continuously measured hourly soil CO 2 fluxes with a 15-channel automated chamber system. The 15 chambers were divided into three groups each with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 33 publications
5
27
1
Order By: Relevance
“…When considering forest soils in Japan, Morisada et al () demonstrated that the mean SOC density of the upper 30 cm forest soil layer was 9.0 kg C m −2 and was about 70% higher than the global average. Previous soil warming studies in the forests of Japan by Aguilos et al () and Teramoto et al () also suggested the possible contribution of high carbon substrate availability for sustaining the stimulatory soil warming effect on R h during five to six years of warming treatments. SOC density at our study site was 11.49 kg C m −2 in the upper 30 cm and slightly higher than that estimated by Morisada et al ().…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…When considering forest soils in Japan, Morisada et al () demonstrated that the mean SOC density of the upper 30 cm forest soil layer was 9.0 kg C m −2 and was about 70% higher than the global average. Previous soil warming studies in the forests of Japan by Aguilos et al () and Teramoto et al () also suggested the possible contribution of high carbon substrate availability for sustaining the stimulatory soil warming effect on R h during five to six years of warming treatments. SOC density at our study site was 11.49 kg C m −2 in the upper 30 cm and slightly higher than that estimated by Morisada et al ().…”
Section: Discussionmentioning
confidence: 86%
“…For example, among the 49 soil warming experiments synthesized by Crowther et al (), only two sites (a grassland and a cropland) were in the Asia‐Pacific region (in China). Recently, soil warming experiments extending over around five‐year periods in the Asian monsoon region have detected no decreasing trend in the stimulatory warming effect, possibly due to substrate depletion or acclimation (Aguilos et al, ; Teramoto et al, ; Wu et al, ). Thus, the response of R h to long‐term warming in the Asian monsoon region might differ to those in Europe and North America.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change scenarios predict an increase in air temperature (by 2.3-4.5 C) in Baltic region (Kont et al, 2003) and soil warming experiments have showed significant enhancement of R s and R h (Bronson et al, 2008;Schindlbacher et al, 2009;Aguilos et al, 2013). Moreover, Aguilos et al (2013) reported enhanced temperature sensitivity of R h in soil warming experiment in cool-temperate forested peatland.…”
Section: Soil Co 2 Effluxesmentioning
confidence: 88%
“…Moreover, Aguilos et al (2013) reported enhanced temperature sensitivity of R h in soil warming experiment in cool-temperate forested peatland. However, some warming studies report either decrease or no significant change in Q 10 values (Bronson et al, 2008;Niinistö et al, 2004).…”
Section: Soil Co 2 Effluxesmentioning
confidence: 96%
“…A test of linearity was applied to control the quality of dC/dt following Aguilos et al 2013 . Simultaneously, soil temperature T s at a depth of 5 cm and volumetric soil water content SWC of the top layer of 5 cm were measured respectively at each plot with a thermocouple probe MHP; Omega Engineering, Stamford, CT, USA and a soil moisture sensor SM150; Delta-T Devices Ltd., Cambridge, UK .…”
Section: Chamber Experimentsmentioning
confidence: 99%